2004
DOI: 10.1111/j.1365-2559.2004.01757.x
|View full text |Cite
|
Sign up to set email alerts
|

Invasive micropapillary carcinoma of the breast: high incidence of lymph node metastasis with extranodal extension and its immunohistochemical profile compared with invasive ductal carcinoma

Abstract: Invasive micropapillary carcinoma of the breast: high incidence of lymph node metastasis with extranodal extension and its immunohistochemical profile compared with invasive ductal carcinoma Aims: Invasive micropapillary carcinoma of the breast is an aggressive and distinctive variant of breast cancer. These tumours have a characteristic histological appearance and have been associated with a high incidence of axillary lymph node metastases and a poor clinical outcome. The aims of this study were to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
112
3
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(140 citation statements)
references
References 16 publications
15
112
3
10
Order By: Relevance
“…The tumor cells show eosinophilic cytoplasm, pleomorphic, hyperchromatic nuclei and a peculiar ''inside-out'' pattern of cell arrangement. [1][2][3][4][5][6][7] Clinicopathological features, summarized in Table 1, include the following parameters: gender and age of the patient, tumor location (proximal or distal to the splenic flexure), macroscopic type (ulcerated/stenosing or polypoid/exophytic), microscopic type (conventional adenocarcinomas or mucinous, when more than 50% of the tumor has an extra-or intracellular mucoid component) 16 and histological grade defined by the ratio of glandular to solid pattern, following the WHO classification 16 and categorizing mucinous adenocarcinoma as grade 3. The extent of tumor invasion and lymph node involvement was assigned according to the TNM system (sixth edition), 17 and the presence or absence of metastasis and peritoneal invasion is reported.…”
Section: Patients Tissues and Clinicopathological Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor cells show eosinophilic cytoplasm, pleomorphic, hyperchromatic nuclei and a peculiar ''inside-out'' pattern of cell arrangement. [1][2][3][4][5][6][7] Clinicopathological features, summarized in Table 1, include the following parameters: gender and age of the patient, tumor location (proximal or distal to the splenic flexure), macroscopic type (ulcerated/stenosing or polypoid/exophytic), microscopic type (conventional adenocarcinomas or mucinous, when more than 50% of the tumor has an extra-or intracellular mucoid component) 16 and histological grade defined by the ratio of glandular to solid pattern, following the WHO classification 16 and categorizing mucinous adenocarcinoma as grade 3. The extent of tumor invasion and lymph node involvement was assigned according to the TNM system (sixth edition), 17 and the presence or absence of metastasis and peritoneal invasion is reported.…”
Section: Patients Tissues and Clinicopathological Featuresmentioning
confidence: 99%
“…It was described first in the breast and ovary, and subsequently in other organs, including the bladder, lung, pancreas and salivary glands. [1][2][3][4][5][6][7] Previously published work found that the proportion of micropapillary carcinoma to the entire tumor ranged from 5 to 80% but was usually less than 30% of the entire lesion, with no pure cases of micropapillary carcinoma reported. Most cases were located in the sigmoid colon and the rectum.…”
mentioning
confidence: 99%
“…Except for the ovary, micropapillary carcinoma arising in many organs seems to pursue an aggressive clinical course because of frequent invasion into lymphatic spaces, metastasis into lymph nodes, or systemic metastasis (Verdú et al;Amin et al, 2002;Amin et al, 1994;Nassar;Nassar et al;Paterakos et al;Siriaunkgul & Tavassoli;Zekioglu et al;Haupt et al;Kim et al;Kuroda et al;Sakamoto et al;Wen et al;Xu et al). Micropapillary carcinoma of the colon macroscopically seems to be indistinguishable from conventional adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The micropapillary carcinoma is regarded as an aggressive variant of adenocarcinoma in any location described, namely bladder, lung, pancreas, salivary glands and recently colon, rectum and stomach (Verdú et al, 2011;Amin et al, 2002;Amin et al, 1994;Nassar, 2004;Nassar et al, 2001;Paterakos et al, 1999;Siriaunkgul & Tavassoli, 1993;Zekioglu et al, 2004). Histologically is characterized by papillary cell clusters surrounded by clear spaces.…”
Section: Introductionmentioning
confidence: 99%
“…Mikropapiller karsinom komponentinin nükleer özellikleri genellikle eşlik eden duktal komponente benzer ve yüksek derecelidir (6)(7)(8)(9)(10)(11). Duktal karsinoma in situ (DKİS) %53-80 oranında görülmekte olup çoğunlukla mikropapiller, kribriform veya papiller tiptedir (1,7,8,18,20).…”
Section: Memeni̇n İnvazi̇v Mi̇kropapi̇ller Karsi̇nomuunclassified